Preparation techniques for zinc ferrites and their applications: A review. (2022) - Pund, Sangita N.; Nagwade, Pratik A.; Nagawade, Arvind V.; Thopate, Shankar R.; Bagade, Arun V.
Abstract: Because of their vast variety of applications, ferrite materials have gained a lot of attention, including catalysts in organic transformations, adsorption, electronic devices, photocatalytic degradations, and gas sensing. This review focuses on zinc ferrites production strategies and their numerous applications. The purpose of this research was to illustrate the advantages and disadvantages of each option of commonly used preparation procedures such as hydrothermal, co-precipitation, solvothermal, micro-emulsion, microwave-assisted, and solid state. This review also focuses on the many characterization techniques used to study the structural, optical, electric, magnetic and dielectric properties of zinc ferrites. This review also discussed their applications in a variety of disciplines, including waste water treatment, photocatalysis, sensors, organic transformation catalysts, LIBs, biomedical devices, and microwave devices.